Enhancement of Wheat Flour and Dough Properties by Non-Thermal Plasma Treatment of Wheat Flour - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio (Applied Sciences, 2022)
Demand to improve food quality attributes without the use of chemicals has risen exponentially in the past few years. Non-thermal plasma (NTP) (also called ‘cold plasma’) is becoming increasingly popular for this purpose due to its unique low-temperature and non-chemical nature. In the present research, the concept of in situ dielectric barrier discharge (DBD) plasma treatment inside a rotational reactor for the direct treatment of wheat flour was experimentally analyzed. The primary research goal was to determine the effects of short-period NTP treatment of DBD type on flour and dough properties. For this purpose, the influence of different operating parameters was tested, i.e., treatment time, the amount of flour placed in the reactor and the environmental (air) temperature. Changes in the structural attributes of the most commonly used flours (type 550 and 1050) and their respective doughs were studied using a set of analytical techniques. Rheological analysis demonstrated the ability of NTP to significantly intensify the visco-elastic properties of dough produced from wheat flour type 550 that was treated for less than 180 s. This indicated that plasma treatment enhanced intermolecular disulphide bonds in gluten proteins, which resulted in stronger protein–starch network formations. However, longer treatment times did not result in a significant increase in the visco-elastic properties of wheat dough. The obtained results showed a 6–7% increase in flour hydration due to NTP treatment, which also makes a contribution to hydrogen bonding due to changes in the bonded and free water phase. Experimental findings further confirmed the dependence of NTP treatment efficiency on environmental air temperature.
CRIS-Team Scopus Importer:2022-09-09
Keywords: dielectric barrier discharge; dough; hydration properties; microstructure; non-thermal plasma; rheology; wheat flour; wheat functionality